Effects of sediment burial on tropical ruderal seagrasses are moderated by clonal integration - Ooi, J.L.S.; Kendrick, G.A.; Van Niel, K.P. (Elsevier, 2011)
Seagrasses are clonal plants that grow submerged in dynamic sedimentary environments where burial is a common occurrence. Clonal organisms may respond to burial in very different ways depending on how strongly integrated they are through horizontal rhizomes, but the effect of clonal integration under conditions of stress such as burial is poorly studied for seagrasses. We test the effect of burial on tropical seagrasses that occur in multispecific meadows by subjecting plants in mixed stands to burial of 0, 2, 4, 8 and 16 cm for 27 days. Treatments were divided into those where rhizomes were severed and those where rhizomes were left intact. We hypothesize that species withstand burial better if clonal integration is maintained (intact rhizomes). Results showed that all species tolerated burial of up to 4 cm without adverse effects but significant reductions in shoot density and biomass become evident at 8 cm of burial. Furthermore, Cymodocea serrulata and Syringodium isoetifolium were strong integrators, i.e. they provide support for buried shoots, whereas Halophila ovalis and Halodule uninervis were weak integrators that did not show evidence of subsidizing buried shoots. Vertical elongation was observed for C. serrulata and H. uninervis as a response to burial only when rhizomes were severed, leading us to speculate on whether species rely on vertical elongation as an escape strategy only in the absence of resource translocation. Our distinction between the responses of treatments with intact rhizomes from those with severed rhizomes may be extended to an interpretation of burial scale (intact rhizomes broad spatial scale burial: severed rhizomes = fine spatial scale burial). We concluded that broad spatial scale burial exceeding 4 cm leads to rapid loss or reduction of all species. However, fine spatial scale burial exceeding 4 cm, such as those caused by shrimp mounds (bioturbation), is expected to favor C. serrulata and S. isoetifolium, while H. ovalis and H. uninervis are disadvantaged. Clonal integration is an important trait in moderating the response of seagrasses to sediment burial and in this way, helps them to cope in high-stress habitats. (C) 2011 Elsevier Ltd. All rights reserved.